2017
DOI: 10.1097/prs.0000000000003881
|View full text |Cite
|
Sign up to set email alerts
|

Superthin SCIP Flap for Reconstruction of Subungual Melanoma: Aesthetic Functional Surgery

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 34 publications
0
68
0
1
Order By: Relevance
“…However, our patients also frequently had donor wound breakdown ( Figure 12). Thin SCIPbased VLVT is theoretically a superior source of vascularized lymph vessels and donor site because 1) its anatomy is familiar to plastic surgeons, 2) it contains higher lymph vessel density than the FDMA donor site, and 3) it has a track record of safety as demonstrated by Hong et al and others [37,[39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…However, our patients also frequently had donor wound breakdown ( Figure 12). Thin SCIPbased VLVT is theoretically a superior source of vascularized lymph vessels and donor site because 1) its anatomy is familiar to plastic surgeons, 2) it contains higher lymph vessel density than the FDMA donor site, and 3) it has a track record of safety as demonstrated by Hong et al and others [37,[39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, defatting after conventional flap elevation would be advantageous for manipulating the superficial fat layer. Also, Lee et al [ 4 ] presented cases where the superficial layer was thicker than the deep fat layer in areas such as the lower abdomen and groin, which are common donor sites for deep inferior epigastric perforator flaps and superficial circumflex iliac artery perforator flaps. Their results showed that effective thinning of the flap may not be possible without manipulation of the superficial fat layer of the donor site in some patients in whom the superficial layer is thicker than the deep fat layer.…”
Section: Discussionmentioning
confidence: 99%
“…Doing so helps to secure flap circulation. The risk of injuring the perforator during primary defatting could be greatly reduced by piecemeal excision of fat lobules in a lobule-by-lobule manner and by minimizing defatting around the point of entry of the perforator after anastomosis [ 4 ]. While a certain level of experience is crucial for harvesting extremely thin flaps, the plane used for elevating the flap is not only relatively precise for eccentrically positioned perforators and easier to elevate than the plane used for thin elevation, but is also better for safe flap perfusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations